PROSES PENETRASI SOSIAL ANTAR PENGGUNA CYBER ACCOUNT DI TWITTER - Nida Fitria Rahmadani (2022)
The presence of new media in various forms, especially social media, has a significant influence on aspects of human life, ranging from seeking and receiving information, exchanging information, doing business, to socializing. This ease of socializing encourages the emergence of the phenomenon of the relationship between cyber account users that is woven through one of the social media, namely Twitter. The main focus of this research is to find out how the process of social penetration among cyber account users is. Therefore, the research theory used is the Social Penetration Theory proposed by Irwin Altman and Dalmas Taylor. The method used is descriptive qualitative, with the type of research that is phenomenology. Data collection techniques used are indirect interview techniques and structured interviews. The final result of this study shows that cyber account users have gone through four stages of social penetration, starting from the orientation stage, the affective exploration stage, the affective exchange stage, to the stable exchange stage. However, not all cyber account users go through these stages thoroughly. In the process of social penetration, cyber account users perform self-disclosure which is motivated by a sense of trust, self-disclosure carried out by the opponent of communication, and a commitment in establishing a relationship.